學科？非學科？綜合活動領域存在的學科價值 Subject? Or Non-Subject? The Subject Value of Integrative Activities Area - 楊宗明 Tsung-Ming Yang (Higher Education Foundation, 2019)
綜合活動學習領域在歷次課程改革過程中有不同的改變，及至《十二年國民基本教育課程綱要總綱》頒布，更名為綜合活動領域，並在國小階段減少授課節數，綜合活動領域的重要性再度受到質疑。然而，從教育社會學觀點來看綜合活動領域，有其價值及意義。本研究透過文獻探討，探究我國綜合活動領域的理論背景，以及歷年課程標準中與綜合活動領域相關的課程安排。研究方法以教育部課程與教學綜合活動領域中央輔導團輔導員的訪談結果，透過紮根理論的主軸編碼整理訪談資料。從主軸編碼中發現綜合活動設定為領域學科的現象，其因果條件包含時間脈絡、國際趨勢、學生學習及理論等，在領域遭受質疑的脈絡中，從歷史、國際、學習、理論及課程加以解釋，並歸納出理論、政策及教師賦權增能的專業強化行動策略，以達到提升教師熱忱與認同的結果。最後，本研究提出我國發展綜合活動領域國小課程發展之反思。 Integrative activities learning area changed with the process of different stages of curriculum reform. However, the name of this field was altered to integrative activities area and the curriculum periods in elementary schools decreased in 12-year basic education curriculum guidelines in 2018. This brings the questioning of the importance of the integrative activities area. Nevertheless, this field has the value and meaning from the perspective of the sociology of education. Through the literature review, the theory background of this field and the integrative activities area related curriculum throughout the history of curriculum reform are investigated. The research method is grounded theory based on the interview with the Ministry of Education Curriculum and Teaching Central Advisors and axial coding was implemented. The findings of the research are as follow. The phenomenon was the integrative activities area being a subject (field) in schools. The causal conditions include time context, international trends, students' learning and theory. While the contextual condition is the questioning of the field, the explanation from the points of history, international context, learning and theory is proposed. The strategic action / interaction in this research is the strengthening of the profession, such as theory, policy and teacher empowerment to reach the consequences of the teachers' enthusiasm and recognition. Finally, reflection on the development of the field is proposed.